The enemies that threaten the real effectiveness of equality plans - Grau Pineda, Carmen (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. It was more than a decade ago since it was approved the Organic Law 3/2007 for the effective equality of women and men, known as the Law of Equality, and it seems sufficient time to take stock of the degree of effectiveness that it has had throughout these years the concrete instrument promoted by her to correct inequality between women and men in business: equality plans. After this time, it seems like an exercise not only interesting but necessary to analyze its most controversial legal aspects, aspects fundamentally referred to its problems of effectiveness or real effectiveness. Critical analysis that always interests to carry out in order to show the successes and failures, the strengths and weaknesses, in order to pro pose the necessary modifications to continue advancing in the genetic objective of the equality plans. There are diverse and varied enemies that hover over their real effectiveness but has decided to devote attention to the three most recurrent: an incorrect diagnosis, an ineffective monitoring and control commission and appropriate content to achieve the desired goal.